Вплив демографічних процесів на формування інвестиційного потенціалу України. - Prokopets, Liudmyla; Babchuk, Antonina; Rudko, Katerina (Прокопець Л.В., Бабчук А.А., Рудько К.І. Вплив демографічних процесів на формування інвестиційного потенціалу України. Науково-виробничий журнал «БІЗНЕС-НАВІГАТОР» 2019. № 5 (54). С. 65-70., 2019)
Економіка України має всі перспективи для стабільного зростання та ефективного розвитку. Зокрема, інвестиції є невід’ємною частиною будь-якого економічного процесу, і, відповідно, інвестиційний потенціал України є цікавою сферою наукових досліджень. Досить багато науковців висвітлювали свої ідеї щодо інвестиційного потенціалу країни, однак необхідно визначити, що формує інвестиційний потенціал в Україні, та чинники, які впливають, і як це може відображати сучасний стан та можливості для нового розвитку. Проаналізувавши наукову літературу, ми вирішили зупинитися на демографічному аспекті. Статтю присвячено визначенню стану та особливостей інвестиційного потенціалу України в сучасних умовах, розкриттю взаємозв’язку між інвестиціями, інвестиційним потенціалом та демографічними чинниками. Досліджено наукові підходи до тлумачення категорії «інвестиційний потенціал», окреслено ключові питання залучення довгострокових інвестицій, запропоновано деякі рекомендації щодо формування сприятливих умов для інвестицій. На основі системи статистичних показників проаналізовано обсяг прямих іноземних інвестицій в Україну, визначено основні країни-інвестори, а також розглянуто розподіл інвестицій між економічними секторами та регіонами України
The economy of Ukraine has all the prospects for sustainable growth and effective development. In particular, investment is an integral part of any economic process, and accordingly, Ukraine's investment potential is an interesting area of research. Quite a number of scholars have covered their ideas about the country's investment potential, but it is necessary to determine what really form the investment potential in Ukraine and the factors that influence it and how it may reflect the current state and opportunities for new development. Having analyzed the scientific literature, we decided to focus on the demographic aspect. The article is devoted to identify the current state and distinctive features of Ukraine's investment potential, revealing the relationship between investment, investment potential and demographic factors. The scientific approaches to the interpretation of the category «investment potential» are explored, the key issues of attracting long-term investments are outlined, and some recommendations are proposed for the creation of favorable conditions for investment. Due to the statistical indicator system we have analyzed the volume of foreign direct investment in Ukraine, have identified the main investor countries to Ukrainian economy, and also we have considered the distribution of investments between economic sectors and regions of Ukraine. The Ukrainian economy will not be able to purport some significant economic inflows from foreign investors until the Ukrainian government solves all social problems and improves the quality of life of the Ukrainian population. For the development of Ukrainian economy, there were outlined the key issues of the attraction of long-term investments and were offered some recommendations regarding the formation of favourable conditions for the investment. On the basis of the system of statistical indicators, there was analysed the volume of foreign direct investment in Ukraine, were determined the main investor countries and the distribution of investments between economic sectors and regions of Ukraine were also scrutinized.
Keywords: демография,; демографічні процеси; демографічні чинники; інвестиції,; інвестиційний потенціал; країни-інвестори; demography; demographic processes; demographic factors; investments,; investment potential,; investor countries.